KKN-PPM LANRISANG MELALUI OPTIMALISASI USAHA MINA-TANI GUNA MENUNJANG PENGEMBANGAN KPPN KABUPATEN PINRANG, PROVINSI SULAWESI SELATAN - Heriansah Heriansah; Nursyahran Nursyahran; Fathuddin Fathuddin (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2019)
KKN-PPM through Optimization of Mina-Tani Business to Support the Development of KPPN in Lanrisang District, South Sulawesi ProvinceAbstract. The KKN-PPM service program is a learning process for students as well as a vehicle for community empowerment. The purpose and benefits of this program are to increase the knowledge and skills of community's to optimally utilizing the potential of resources, increase the technical competence of students in community empowerment, and increase the acceleration of the regional development process, particularly the development of the Kawasan Perdesaan Prioritas Nasional (KPPN). KKN-PPM is carried out in Lanrisan Village, Lerang Village, Waetuoe Village, Lanrisang District, Pinrang Regency. Technologies applied through the KKN-PPM work program include nitrobacter-based milkfish culture technology, minapadi cultivation, aquaponics cultivation, waste utilization for creative products and fish feed, diversification of processed fish, early education about fisheries and marine for school students and socialization likes to eat fish (GEMARI), as well as the development of beach tourism. Program implementation partners are the sub-district and village governments and fisheries extension agents with target audiences of farmer groups, housewife groups and school students. The model of the program implementation approach is Participatory Rural Appraisal, Participatory Technology Development, and Community Development with non-technical counseling methods, technical counseling, as well as demonstration and field practice on the pilot land. The results achieved in this activity were increased knowledge and skills of the target audience in implementing several aquaculture systems and diversification of fish preparations and the use of waste into creative products and fish feed, there were several examples of aquaculture, GEMARI program socialization, early reduction of fisheries and marine to school students, and the availability of beach tourism support facilities.Keywords: Optimization, mina-tani National Priority Rural Areas, demonstration landAbstrak. Program pengabdian KKN-PPM merupakan proses pembelajaran bagi mahasiswa sekaligus wahana pemberdayaan masyarakat. Tujuan dan manfaat program ini adalah meningkatkan pengetahuan dan keterampilan masyarakat dalam memanfaatkan potensi sumberdaya secara optimal, meningkatkan kompetensi teknis mahasiswa dalam pemberdayaan masyarakat, dan meningkatkan percepatan proses pembangunan daerah, khususnya pengembangan Kawasan Perdesaan Prioritas Nasional (KPPN). KKN-PPM dilaksanakan di Kelurahan Lanrisan, Desa Lerang, Desa Waetuoe Kecamatan Lanrisang Kabupaten Pinrang. Teknologi yang diterapkan melalui program kerja KKN-PPM antara lain teknologi budidaya ikan bandeng berbasis nitrobakter, budidaya minapadi, budidaya akuaponik, pemanfaatan sampah/limbah untuk produk kreatif dan pakan ikan, diversifikasi olahan ikan, edukasi dini tentang perikanan dan kelautan bagi siswa sekolah dan sosialisasi gemar makan ikan (GEMARI), serta pengembangan wisata pantai. Mitra pelaksanaan program adalah pemerintah kecamatan dan desa serta penyuluh perikanan dengan khalayak sasaran kelompok tani, kelompok ibu rumah tangga, dan siswa sekolah. Model pendekatan pelaksanaan program adalah Participatory Rural Appraisal, Participatory Tecnology Development, dan Community Development dengan metode penyuluhan non teknis, penyuluhan teknis, serta demonstrasi dan praktek lapang di lahan percontohan. Hasil yang dicapai pada kegiatan ini adalah meningkatnya pengetahuan dan keterampilan khalayak sasaran dalam menerapkan beberapa sistem budidaya dan diversifikasi olahan ikan serta pemanfaatan sampah/limbah menjadi produk kreatif dan pakan ikan, terdapatnya beberapa percontohan budidaya, tersosialisasinya program GEMARI, teredukasinya secara dini tentang perikanan dan kelautan kepada siswa sekolah, dan terdapatnya fasilitas pendukung wisata pantai.Kata Kunci: Optimalisasi, mina-tani, Kawasan Perdesaan Prioritas Nasional, lahan percontohan